2016
DOI: 10.1093/icesjms/fsw185
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic target strength (TS) of argentine anchovy (Engraulis anchoita): the nighttime scattering layer

Abstract: Engraulis anchoita is a physostomous fish with a dual chambered swimbladder (sb). In situ target strength (TS) measurements on this species are only possible at night, when anchovies disperse forming a scattering layer near the sea surface. A survey data series comprising more than 50000 single target detections, recorded from 1995 to 2008, was analyzed in order to study the species specific TS at 38 kHz. A TS vs. fish total length (L) equation was obtained from the in situ measurements (TS = 31.9 log L – 82.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In these cases, considering the BEM solution as a benchmark, the FEM model enhances the capability in detecting small variations in the swimbladder shape. Our results demonstrated the inter-individual variability and the high bias due to the tilt angle of the fish in broadband pattern proved by other authors on engraulidae species 51,53 . Accordingly, model results can be useful to interpret the tilt angle displacement of the fish during in situ measurements.…”
Section: Discussionsupporting
confidence: 80%
“…In these cases, considering the BEM solution as a benchmark, the FEM model enhances the capability in detecting small variations in the swimbladder shape. Our results demonstrated the inter-individual variability and the high bias due to the tilt angle of the fish in broadband pattern proved by other authors on engraulidae species 51,53 . Accordingly, model results can be useful to interpret the tilt angle displacement of the fish during in situ measurements.…”
Section: Discussionsupporting
confidence: 80%
“…Theoretical and empirical experiments proved that the peak of backscatter in fish with swimbladder is achieved at a negative tilt angle of ~ 10°, followed by a drop at steeper angles characterized by individual-fish pattern 35 , 53 , 56 . S. colias displays a TS pattern against tilt angle characterized by modest variation along the tilt angles reaching a peak at around − 4° at 38 kHz.…”
Section: Discussionmentioning
confidence: 97%
“…New TS-TL relationships derived from models are seldom employed for acoustic abundance estimates 53 . Most frequently, models are exploited for comparison purposes with ex-situ or in-situ experiments 32 , 33 , 56 , 57 . The relationship found in this work can be compared with the study carried out on these species by Palermino et al 58 .…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the body tilt distribution for fish is of utmost importance for fisheries acoustics, given that backscattering strength is mainly originated at the exposed fish area. We tested the present hydrodynamical model against in-situ TS measurements and simulated data for Argentine Anchovy (Madirolas et al, 2016). In this case, the lack of the observed TS with depth cannot be just explained by swimbladder compression, thus we associated this difference with a body tilting excursion.…”
Section: Depthmentioning
confidence: 99%
“…An example with Argentine anchovyIn this section we shall study the previous implications for a particular fish: Argentine anchovy. We are particularly interested in this fish because recently inMadirolas et al (2016) there were reported in situ Target Strenght (TS ) measurements where they suggested an increasing body tilting behaviour with depth. Furthermore, in this work it was obtained a tilting vs depth behaviour by simulating theoretical TS functions for some scenarios of swimbladder contraction and tilt angle distributions.…”
mentioning
confidence: 99%